2016
DOI: 10.1017/sjp.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of a Spanish Version of the Multidimensional Inventory of Religious/Spiritual Well-Being in Mexican College Students

Abstract: After the Multidimensional Inventory for Religious/Spiritual Well-Being (MI-RSWB) was validated as a reliable instrument for the Western European context it is primarily intended in this study to translate the measure into Spanish and adapt it for the Mexican culture. Furthermore we investigate whether spirituality/religiosity has a similar impact on indicators of personality and subjective well-being in Mexico as it does in samples drawn from Western European cultures. 190 students (99 females) from public an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
2
8
2
Order By: Relevance
“…The Brief Religious Coping (B-RCOPE) [ 5 , 6 ] has been largely used to assess religious coping. This instrument developed by Pargament and colleagues, and has been translated and validated in a number of languages including Arab [ 7 ], Iranian [ 8 ], Polish [ 9 ], and Spanish [ 10 ] as well as in several religions and doctrines including Protestants and Catholics [ 6 ], Hindus [ 11 ], and Jewish [ 12 ]. According to Pargament’s theory of religious coping, religious coping refers to the way one may understand and overcome stressful life situations using approaches related to the sacred [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brief Religious Coping (B-RCOPE) [ 5 , 6 ] has been largely used to assess religious coping. This instrument developed by Pargament and colleagues, and has been translated and validated in a number of languages including Arab [ 7 ], Iranian [ 8 ], Polish [ 9 ], and Spanish [ 10 ] as well as in several religions and doctrines including Protestants and Catholics [ 6 ], Hindus [ 11 ], and Jewish [ 12 ]. According to Pargament’s theory of religious coping, religious coping refers to the way one may understand and overcome stressful life situations using approaches related to the sacred [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The B-RCOPE has been administered to several populations including adolescents [ 9 ], college students [ 10 ], patients undergoing cardiac surgery [ 16 ], cancer patients and their caregivers [ 17 , 18 ], and medically ill elderly hospitalized patients [ 19 ], among others. Overall, PRC has been associated with favorable outcomes after exposure to stressful events [ 19 ] including but not limited to better overall quality of life and less symptoms of psychological distress (e.g., anxiety and depression).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the MI-RSWB has been proven to be significantly related to other prominent measures of religiosity, such as the "Centrality of Religiosity" C-Scale (CRS; Huber and Huber, 2012). Thereby, for instance, Berger et al (2016) reported positive links between CRS and all MI-RSWB scores except HT.…”
Section: Introductionmentioning
confidence: 98%
“…The latter resulted in norm values for the Austrian general population, with appealing psychometric properties for the subscales and the total score ( Unterrainer and Fink, 2013 ). So far, the questionnaire has been translated into and validated in English ( Unterrainer et al, 2012 ), Italian ( Stefa-Missagli et al, 2014 ), Mexican Spanish ( Berger et al, 2016 ), Bosnian ( Malinovic et al, 2016 ), Russian ( Agarkov et al, 2018 ), and Farsi ( Dadfar et al, 2019 ), thereby demonstrating satisfactory psychometric properties (with one exception for HT in Dadfar et al, 2019 ). However, confirmatory factor analysis of data obtained in Austrian ( Unterrainer et al, 2010 ) and British samples ( Unterrainer et al, 2012 ) revealed only limited empirical support for the original MI-RSWB structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently it was observed, that General Religiosity, when paired with a disrupted personality structure, to be the strongest predictor of Religious Fundamentalism (Unterrainer et al, 2016). Meanwhile the original Austrian-German version of the scale has been successfully adapted into several different languages such as Bosnian (Malinovic, Fink, Lewis, & Unterrainer, 2016), English (Unterrainer, Nelson, Collicutt, & Fink, 2012), Italian (Stefa-Missagli, Huber, Fink, Sarlo, & Unterrainer, 2014) and Mexican-Spanish (Berger, Fink, Perez, Lewis, & Unterrainer, 2016). Moreover several additional studies in clinical surroundings were conducted by investigating various groups of general medical as well as psychiatric patients (Unterrainer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%